Uso do EPANET 2.0 na avaliação hidráulica de sistemas de irrigação por pivô central - Baptista, Victor Buono Silva (2017)
Areas irrigated by center pivot aspersion systems represent approximately 20% of the area irrigated in Brazil. The growth in this demand justifies the need for more thorough studies on irrigation systems to enhance hydraulic projects. The use of computational tools to simulate and assess irrigation systems facilitates the evaluation of hydraulic parameters. Software EPANET 2.0 is a hydraulic simulation tool developed for the analysis of water distribution networks and may be used in pressurized irrigation systems, since it is provided with components like: reservoirs, pumps, pipes, valves, and emitters, among others, which are tools necessary in an irrigation system. Using EPANET 2.0 may be disadvantageous, though, due to the edition of input data required to arrange the center pivot irrigation system. Because this equipment has many components, such edition may become very troublesome and require another tool to edit input data on EPANET 2.0. This work aimed at creating an app, based on routines of Excel’s Visual Basic for Applications (VBA), that allows editing input data to the center pivot equipment on EPANET 2.0, and then comparing the numbers obtained from such hydraulic simulation on EPANET 2.0 with results from pressure distribution analysis throughout the lateral line, using analytical methods. The numbers obtained on EPANET 2.0 were very close to those obtained from analytical methods, making it feasible to use it as a tool of hydraulic simulation and assessment of center pivot irrigation systems.